Filosofie als praktijk. Krisis na 40 jaar - Ido de Haan (University of Groningen Press, 2020)
In its forty years of existence, Krisis, as a journal of contemporary philosophy, has aimed to develop a new philosophical praxis. This praxis is sketched here in the first place as the practical work of making a journal, in the context of a community of philosophers discussing a canon of contemporary thinkers as well a range of shared problems. Yet beyond that, Krisis has always struggled with the question how, as a philosophical practice, it is related to other practices. The debate about “empirical philosophy” forms a crucial episode in this debate, in which Krisis has explored analytical, existentialist, pragmatist and Marxist approaches to a philosophy as praxis. Since then, this debate has shifted along four dimensions, of science, culture, politics and economy. In conclusion, it is argued that the entanglement of the praxis of Krisis with these four other practices makes it difficult to identify what is philosophical about Krisis.